Advances in Grid and Pervasive Computing [electronic resources]: Second International Conference, GPC 2007, Paris, France, May 2-4, 2007. Proceedings - GPC 2007 (2007 : Paris, France); Cerin, Christophe; Li, Kuan-Ching; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
57